Management of women with infertility and uterine leiomyoma in assisted reproductive technology programs - S. V. Khmil; Yu. B. Drozdovska (Kazimierz Wielki University, 2020)
In the structure of female infertility, one of the important causes is the uterine factor of infertility, namely, uterine leiomyoma, which is diagnosed in 13.3-24.0% of cases and leads to loss of reproductive function and pregnancy pathology. Aim of research: to increase the incidence of pregnancy in infertile women with uterine leiomyoma by analyzing the main factors in the development of this pathology and optimizing the treatment and prevention complex. Material and research methods. A randomized clinical trial was performed among 175 (29.0%) women of reproductive age with a UL diagnosis, and the control group (CG) of 32 somatically healthy women with normal menstrual and reproductive functions, who were divided into the following groups: Main Group A (MG) - 137 women with UL, who were further divided into subgroups for evaluation of the treatment: subgroup A1 - 55 women with UL after laparoscopy and hysteroscopy with the proposed treatment complex (TC), subgroup A2 - 45 women with UL after hysteroscopy and TC, subgroup A3 - 37 women with UL and the proposed drug treatment without surgical removal of UL; comparison group B - 38 women with UL and conventional treatment. Results. The age of the examined patients was (33.9 ± 7.8) years (26-42 years), BMI - (23.5 ± 5.2) kg / m², AMH - 1.8 ng / ml (0.4-5), 2 ng / ml). The duration of infertility was 2-15 years on average (5.4 ± 0.5 years). Primary infertility was diagnosed in 43 patients (24.5%), and secondary - in 132 women (75.5%). 93 (53.7%) women developed hypermenorrhea, of which one in three indicated a history of anemia. 31 (17.7%) women complained of algodysmenorrhea; in 43 (24.6%) women, dysmenorrhea occurred after the appearance of uterine fibroids, and 23 women (13.2%) had irregular menstruation. During hysteroresectoscopy, single submucosal nodes "on the pedicle", which had clear contours, a rounded shape, a dense consistency, and deformed the uterine cavity, were found in 71 (40.8%) patients. Of these, 51 (71.8%) nodes were whitish in color with isolated small hemorrhages, and in the remaining 20 (28.2%) cases, the nodes were covered with a lace of stretched and altered blood vessels. Analysis of the location and size of the nodes revealed that in every third patient (25 patients, 35.2%) the size of the node was about2.5 cm, in every fourth (19 patients, 26.7%) nodes were up to4 cm, in other patients (27 patients, 38.0%) the nodes were up to5 cmand greater in size Interstitial-submucosal myomas with a combination of subserous nodes were diagnosed in 104 (59.2%) of the examined women and visualized as a bulge of one of the uterine walls. During hysteroresectoscopy, we visualized endometrial hyperplasia in 89 (50.8%) patients, which was subsequently confirmed histologically in 67 (38.3%) women, and secretory transformation of the endometrium in the remaining 22 (12.5%). In 22 (12.6%) patients, we observed hysteroscopic signs of chronic endometritis; this diagnosis was also confirmed morphologically, which was manifested by uneven thickening of the endometrium and micropolyps. The use of our improved algorithm of rehabilitation measures allowed to reduce the period of menstrual bleeding in 42 (48.8%) women in group A2, which was 1.3 times more effective than in the comparison group and 1.4 times more effective than in patients of group A3. Menstrual discharge was 1.9-fold and 1.8-fold lower compared to A1 women who refused surgery and 1.2-fold lower than in the comparison group. The effectiveness of the proposed treatment was analyzed, and the frequency of pregnancy was evaluated; findings indicate that the highest efficiency was observed in women of group A2 - 31.1% of cases, which was 2 times higher than the comparison group and 2.3 times higher than in group A3. Conclusion. Uterine leiomyoma is mainly the cause of infertility due to a mechanical factor. Laparo- and hysteroresectoscopy is the optimal method of pre-pregnancy treatment for women with uterine leiomyoma who are undergoing infertility treatment with assisted reproductive technologies. Laparo- and hysteroresectoscopy is an organ-sparing operation that has a number of advantages: easy postoperative period, no adhesions, which, in turn, increases the frequency of pregnancy and reduces premature delivery.